Apoptotic and Antiapoptotic Effects of CXCR4: Is It a Matter of Intrinsic Efficacy? Implications for HIV Neuropathogenesis - KHAN, MUHAMMAD Z. (2004)
CXCR4, the specific receptor for the chemokine SDF-1α that also binds CXCR4-using HIV gp120s, affects survival of different cell types, including neurons. However, current data show that the outcome of CXCR4 activation on neuronal survival may vary depending on the ligand and/or the cellular conditions. In this study, we have systematically compared the effects of SDF-1α and gp120(IIIB) (with or without CD4) on several intracellular pathways involved in cell survival, including MAP kinases and Akt-dependent pathways. Our data show that gp120(IIIB) and SDF-1α are both potent activators of MAP kinases in neuronal and non-neuronal cells, though the kinetic of these responses is slightly different. Furthermore, unlike SDF-1α, and independently of CD4, gp120(IIIB) is unable to stimulate Akt and some of its antiapoptotic targets (NF-κB and MDM2)—despite its ability to activate other signaling pathways in the same conditions. Finally, the viral protein is more efficient in recruiting some effectors (e.g., JNK) than others in comparison with SDF-1α (EC(50) = 0.1 vs. 0.6 nM). We conclude that the intrinsic efficacy of the two ligands is significantly different and is pathway dependent. These findings have important implications for our understanding of CXCR4-mediated responses in the CNS, as well as the role of this coreceptor in HIV neuropathogenesis.